2017
DOI: 10.1016/j.virol.2017.06.033
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor SAHA simultaneously reactivates HIV-1 from latency and up-regulates NKG2D ligands sensitizing for natural killer cell cytotoxicity

Abstract: In pilot HIV-1 eradication studies, patients' immune responses were ineffective at killing viral reservoirs reactivated through latency reversing agents (LRAs) like suberoylanilide hydroxamic acid (SAHA). We hypothesized that T cells harboring reactivated HIV-1 express MIC and ULBP ligands for the activating NKG2D receptor of natural killer (NK) cells. Here, we demonstrated that MICA/B and ULBP2 are induced by SAHA on primary T cells harboring reactivated virus. Using latently HIV-1-infected J-Lat 6.3/8.4/9.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 75 publications
6
27
0
Order By: Relevance
“…NK cells can also kill antibody-coated targets via ADCC and regulate immune responses via cytokines and chemokines production as well as by cell-to-cell interactions ( 26 ). Work from various laboratories including our own has shown that HIV-1-infected T cells are exposed to NK cell recognition and killing due to virus-induced upregulation of ligands for the activating NKG2D receptor ( 27 31 ), a phenomenon that is maintained also in latently infected CD4 + T cells once the virus is reactivated, as we showed in a recent report ( 32 ). Of note, in a clinical trial employing Panobinostat to reverse HIV-1 latency in patients on ART, the expansion of activated NK cells, not HIV-1-specific CTLs, was the major correlate of viral DNA decline ( 33 ).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…NK cells can also kill antibody-coated targets via ADCC and regulate immune responses via cytokines and chemokines production as well as by cell-to-cell interactions ( 26 ). Work from various laboratories including our own has shown that HIV-1-infected T cells are exposed to NK cell recognition and killing due to virus-induced upregulation of ligands for the activating NKG2D receptor ( 27 31 ), a phenomenon that is maintained also in latently infected CD4 + T cells once the virus is reactivated, as we showed in a recent report ( 32 ). Of note, in a clinical trial employing Panobinostat to reverse HIV-1 latency in patients on ART, the expansion of activated NK cells, not HIV-1-specific CTLs, was the major correlate of viral DNA decline ( 33 ).…”
Section: Introductionsupporting
confidence: 64%
“…Aliquots (2 µg) of total RNA were used to generate cDNA using random hexamers, and the resulting cDNA (25 ng) was amplified in triplicate using the SensiFAST SYBR Green PCR master mix (all from Bioline). The qPCR reactions were performed using primers for MICA, MICB, ULBP2, and PIGS as previously described ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, valproic acid, a weak HDAC inhibitor, upregulates NKG2D ligands only in malignant cells, where the ligands are present at baseline (42). However, initial in vitro studies in HIV-infected cell lines suggested that VOR could also upregulate certain NKG2D ligands (43), which in addition may play an important role in facilitating NK-mediated ADCC responses (44). Finally, novel latency-reversing agents, such as Toll-like receptor (TLR) agonists, may simultaneously reverse HIV latency and improve NK cell function (45,46), although further study is needed to definitively determine the effect of TLR agonists on NK cells, given the multiple and direct effects that these drugs might have on immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrating diverse responses of infected cells to LRAs point to their weak effect (Archin et al, 2012;Spivak et al, 2014;Elliott et al, 2015) and highlight the diversity of determinants responsible for the reservoirs' heterogeneity that were demonstrated so far to be virus genetic background- (Norton et al, 2019), cell model- (Spina et al, 2013), cell type- (Baxter et al, 2016;Grau-Expósito et al, 2019;Kula et al, 2019), silencing mechanism- (Elliott et al, 2014;Yukl et al, 2018), tissue reservoir- (Elliott et al, 2014;Telwatte et al, 2018;Yukl et al, 2018), integration site- (Chen et al, 2017;Abner et al, 2018;Battivelli et al, 2018), patient- (Darcis et al, 2017;Yukl et al, 2018), and gender- (Das et al, 2018) specific. In addition, some studies demonstrate a heterogeneous effect of LRAs on NK cells (Garrido et al, 2016) and cytotoxic T-cell lymphocyte (Walker-Sperling et al, 2016) activity with conflicting observations, suggesting either an immunosuppressive effect or a reduced impact of LRA activity on cells sensing HIV-1 reactivation (Archin et al, 2012;Jones et al, 2014;Clutton et al, 2016;Walker-Sperling et al, 2016;Desimio et al, 2017Desimio et al, , 2018. Moreover, prolonged ART treatment is associated with a significant reduction in the frequency of HIV-1-specific CD8 + T-cells (Gray et al, 1999;Casazza et al, 2001).…”
Section: Resultsmentioning
confidence: 99%